Biodegradation of bisphenol A and decolorization of synthetic dyes by laccase from white-rot fungus, trametes polyzona - Chairin T. (2014)
Purified laccase from Trametes polyzona WR710-1 was used as biocatalyst for bisphenol A biodegradation and decolorization of synthetic dyes. Degradation of bisphenol A by laccase with or without redox mediator, 1-hydroxybenzotriazole (HBT) was studied. The quantitative analysis by HPLC showed that bisphenol A rapidly oxidized by laccase with HBT. Bisphenol A was completely removed within 3 h and 4-isopropenylphenol was found as the oxidative degradation product from bisphenol A when identified by GC-MS. All synthetic dyes used in this experiment, Bromophenol Blue, Remazol Brilliant Blue R, Methyl Orange, Relative Black 5, Congo Red, and Acridine Orange were decolorized by Trametes laccase and the percentage of decolorization increased when 2 mM HBT was added in the reaction mixture. This is the first report showing that laccase from T. polyzona is an affective enzyme having high potential for environmental detoxification, bisphenol A degradation and synthetic dye decolorization. © 2012 Springer Science+Business Media New York.